Investigation of Isoelectronic Doping in p-GaN Based on the Thermal Quenching of UVL Band - Yang Huang; Zhiqiang Liu; Xiaoyan Yi; Yao Guo; Guodong Yuan; JunXi Wang; Guohong Wang; Jinmin Li (IEEE Photonics Journal)
In this paper, isoelectronic doping with indium (In) in p-GaN is investigated on the basis of the thermal quenching of ultraviolet luminescence (UVL) band. A phenomenological rate-equation model is proposed as a nondestructive diagnostic technique to acquire the dopant ionization energy of p-GaN. In terms of this model, we analyze the evolution of the ionization energy of p-GaN samples grown with different trimethyindium flow rate and find that isoelectronic doping with appropriate In incorporation is able to significantly reduce the ionization energy of the acceptor from 245 to 112 meV, which are consistent with the results of the variable temperature Hall-effect measurements. The comparison between the samples’ full width at half maximum of the UVL band indicates that excessive In incorporation will degenerate the conductivity of p-GaN.